All about the weather - Henderson, Jason; Rodriguez, Carlo; Routh, Jude L.
This video explains what each is and goes on to discuss the various cloud formations that appear in our planet's atmosphere. Aspects of weather such as temperature, humidity, precipitation, wind, and air currents are addressed. Finally, we focus on weather as a powerful force of nature, as we look at thunderstorms, tornadoes, and hurricanes.